URGENSI PENDIDIKAN ISLAM DALAM PENGUATAN IDENTITAS KEISLAMAN PADA PEREMPUAN, ANAK, DAN REMAJA - nurchasanah; moh. roqib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic education plays a crucial role in shaping and strengthening the Islamic identity of women, children, and adolescents through a comprehensive, contextual, and adaptive approach to the challenges of the times. This enables them to be equipped with strong spiritual, moral, and intellectual values. Supported by family, educational institutions, technology, and favorable policies, Islamic education can serve as a solid foundation for maintaining and developing the Muslim identity in facing the dynamics of modern social and cultural life. This study uses a qualitative method. The results show that Islamic identity is an essential foundation in forming a strong and integrous Muslim character, developed through a systematic and sustainable Islamic education process. Islamic education holds great urgency in confronting globalization challenges by providing women, children, and adolescents with comprehensive religious understanding and strong moral values, enabling them to preserve their identity amidst social dynamics. Therefore, strategies for strengthening Islamic identity must be implemented holistically by involving families, communities, educational institutions, and utilizing technology, supported by role models and appropriate policies so that the younger generation can internalize and practice Islamic values meaningfully in daily life. Keywords : Islamic Education; Islamic Identity; Women; Children; Adolescents